2015
DOI: 10.1007/s00190-015-0817-1
|View full text |Cite
|
Sign up to set email alerts
|

The status of measurement of the Mediterranean mean dynamic topography by geodetic techniques

Abstract: We review the measurement of the mean dynamic topography (MDT) of the Mediterranean using ellipsoidal heights of sea level at discrete tide gauge locations, and across the entire basin using satellite altimetry, subtracting estimates of the geoid obtained from recent models. This 'geodetic approach' to the determination of the MDT can be compared to the independent 'ocean approach' that involves the use of in situ oceanographic measurements and ocean modelling. We demonstrate that with modern geoid and ocean m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…We first note that geodetic and ocean MDTs agree on the $3-7 cm level. This is an encouraging observation, as similar studies for tide gauges along other coasts have shown an agreement between geodetic and ocean MDTs on the $6-14 cm level [e.g., Woodworth et al, 2012Woodworth et al, , 2015. Higginson et al [2015] got an agreement between geodetic and ocean MDTs of 2.3 cm along the east coast of North America; however, this number resulted from mean geodetic and ocean MDTs based on 7 geoid models and 11 ocean models, respectively.…”
Section: Comparative Assessmentsupporting
confidence: 66%
See 4 more Smart Citations
“…We first note that geodetic and ocean MDTs agree on the $3-7 cm level. This is an encouraging observation, as similar studies for tide gauges along other coasts have shown an agreement between geodetic and ocean MDTs on the $6-14 cm level [e.g., Woodworth et al, 2012Woodworth et al, , 2015. Higginson et al [2015] got an agreement between geodetic and ocean MDTs of 2.3 cm along the east coast of North America; however, this number resulted from mean geodetic and ocean MDTs based on 7 geoid models and 11 ocean models, respectively.…”
Section: Comparative Assessmentsupporting
confidence: 66%
“…Jayne [] as well as Woodworth et al . [] underline the importance of not mixing altimetry‐derived gravity information in a quasigeoid model for MDT estimation purposes, as some of the dynamic topography will blend into the quasigeoid model, corrupting the MDT estimate when combined with the ocean's time‐mean surface from altimetry or tide gauges. In this respect, there is a considerable difference between NMA2014 and EGM2008.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations